Generation of human induced pluripotent stem cell lines (hiPSC) from one bipolar disorder patient carrier of a DGKH risk haplotype and one non-risk-variant-carrier bipolar disorder patient - Viola Stella Palladino; Nadia Omega Cipta Subrata; Andreas Geburtig-Chiocchetti; Rhiannon McNeill; Per Hoffmann; Andreas Reif; Sarah Kittel-Schneider (Stem Cell Research, 2018)
Fibroblasts were isolated from skin biopsies from two patients with bipolar I disorder. One patient was a 26 year old female carrying a risk haplotype in the DGKH (diacylglycerol kinase eta) gene and the other was a non-carrier 27 year old male. Patient fibroblasts were reprogrammed into human induced pluripotent stem cells (hiPSCs) by using a Sendai virus vector. DGKH-risk haplotype and non-risk haplotype hiPSCs showed expression of pluripotency markers and were able to differentiate into cells of the three germ layers. These cell models are useful to investigate the role of risk gene variants in bipolar disorder.Resource table.Unlabelled TableUnique stem cell lines identifierKGUi001-AKGUi002-AAlternative names of stem cell linesAR1023 hiPSC (KGUi001-A)AR1034 hiPSC (KGUi002-A)InstitutionDepartment of Psychiatry, Psychosomatic Medicine and Psychotherapy, University Hospital Frankfurt, Frankfurt Am Main, GermanyContact information of distributorDr. Sarah Kittel-Schneider, sarah.kittel-schneider@kgu.deType of cell linesiPSCOriginHumanCell SourceDermal fibroblastsClonalityClonalMethod of reprogrammingSendai virusMultiline rationaleSame disease non-isogenic cell linesGene modificationNoType of modificationN/AAssociated diseaseBipolar DisorderGene/locusSNPs DGKH (rs994856/rs9525580/rs9525584 GAT haplotype; GG/AG/TT) and NON-GAT haplotype (AG/GG/CT); 13q14.11Method of modificationN/AName of transgene or resistanceN/AInducible/constitutive systemN/ADate archived/stock dateMay 2018Cell line repository/bankN/AEthical approvalEthics committee University of Würzburg, 10.06.2011, Ethical approval number 96/11Ethics committee University of Frankfurt, 04.3.2015, Ethical approval number 425/14